Identification, functional analysis, prevalence and treatment of monocarboxylate transporter 8 (MCT8) mutations in a cohort of adult patients with mental retardation. (7th January 2013) - Visser, W. Edward; Vrijmoeth, Paul; Visser, Frank E.; Arts, Willem Frans M.; van, Hans; Visser, Theo J.
Summary Objective Monocarboxylate transporter 8 (MCT8) is an essential thyroid hormone (TH) transporter as humans with MCT8 mutations have severe neurological and endocrine abnormalities. The objectives are (i) to identify novel MCT8 mutations and (ii) to assess their functional relevance; (iii) to describe the effects of block‐and‐replace treatment in an MCT8 patient. Design The TOP‐R study is a cross‐sectional nation‐wide multicentre study. Patients Subjects with unexplained mental retardation (MR) were screened for MCT8 mutations. Results We identified three mutations: p.F501del (previously described), p.L492P and p.T162T. The F501del and L492P mutants, but not the T162T mutant, showed diminished T3, T4 and rT3 transport in transfected cells. TH transport in T162T fibroblasts was also not affected. One patient was treated with block‐and‐replace therapy to normalize serum TH levels. The results indicated a slow onset of the decrease in serum T4 and T3 by successive treatment with methimazole and PTU, and eventually their complete normalization by administration of LT4 with PTU but not with methimazole. The frequency of MCT8 mutations in males with X‐linked MR approximately 3·9%. Conclusions We identified several MCT8 mutations in a cohort of subjects with unexplained MR. We demonstrated the pathogenicity of two missense mutations. The synonymous variant did not affect TH transport. Block‐and‐replace therapy of one patient reversed the TH abnormalities. Our data suggest a decreased TH secretion rate and an increased T4 to T3 conversion by the type I deiodinase in patients with MCT8 mutations. Our study indicates that MCT8 mutations are a relatively frequent cause of X‐linked MR.